The Influence of Double-Date Promotional Events and Financial Technology Literacy on Students' Financial Management Behavior: The Mediating Role of Self-Control - Nur Qholila; Novien Rialdy (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
The rapid growth of e-commerce and digital financial services has transformed students' purchasing behavior, particularly during double-date promotional events. Although previous studies have extensively examined promotional campaigns, financial technology literacy, and consumer behavior, limited evidence explains how these factors jointly influence students' Financial Management Behavior through the mediating role of Self-Control. Therefore, this study investigates the effects of Double-Date Promotional Events and Financial Technology Literacy on students' Financial Management Behavior, with Self-Control serving as an intervening variable. This study employed a quantitative research design involving Management students at Universitas Muhammadiyah Sumatera Utara. The sample was determined using the Slovin formula, and data were collected through structured questionnaires. The proposed research model was analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that Double-Date Promotional Events, Financial Technology Literacy, and Self-Control significantly influence students' Financial Management Behavior. In addition, Double-Date Promotional Events and Financial Technology Literacy significantly affect Self-Control, which further mediates their relationships with Financial Management Behavior. These findings demonstrate that students' financial management is influenced not only by external promotional stimuli but also by digital financial capability and individual self-regulation.This study contributes to the literature by integrating Double-Date Promotional Events, Financial Technology Literacy, and Self-Control into a single conceptual framework explaining students' Financial Management Behavior. The findings also provide practical implications for universities and digital financial service providers in strengthening financial literacy and promoting responsible financial decision-making among university students.